Modeling the Effects of Hydrodynamics on Thermal Stratification and Algal Blooms in the Xiangxi Bay of Three Gorges Reservoir - Xu, Hui; Yan, Meng; Long, Lianghong; Ma, Jun; Ji, Daobin; Liu, Defu; Yang, Zhengjian (Frontiers in Ecology and Evolution, 2021)
Algal blooms have been reported in some tributary bays since the initial impoundment of Three Gorges Reservoir, which has seriously affected the surrounding area’s water ecology and drinking water safety. Hydrodynamics plays a crucial role in algae growth. The recently numerical model of hydrodynamics and algal blooms is an effective method to identify the effects of hydrodynamics on phytoplankton and find potential strategies for controlling algal blooms. In this study, the CE-QUAL-W2 model was developed to simulate the hydrodynamics and algal blooms in Xiangxi Bay (XXB) of the Three Gorges Reservoir. The model performed well in simulating flow patterns, water temperature profiles, and algal blooms. The results indicated that the hydrodynamics showed significant spatial and temporal differences in the XXB. In the mouth area, the intensity and plunge depth of density current were dynamic and characterized by a typical seasonal pattern. The changes in density currents will provide more opportunities for vertical mixing, resulting in un-stratification and low risk of algal blooms. But in the middle and upper areas, strong stratification and low velocity at upstream provide enough favorable conditions for the growth of algae and increase the risk of algal blooms. The simulation results revealed the variation of mixing depth could be good for clarifying the spatial and temporal differences of Chl.a. It played a vital role in seasonal stratification and the dynamics of phytoplankton succession in XXB. To improve the understanding of mixing regimes would be helpful to understand the physical mechanism of algal blooms elimination.